Preventive maintenance pada mesin die casting dengan age replacement model untuk peningkatan reliabilitas mesin - Andriani Andriani; Ikhsan Romli (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
In an industry, the maintenance department plays a very important role in ensuring the smooth production process. The method of machine maintenance with preventive maintenance is a strategy that can be used to repair existing machines. This is related to proper and regular maintenance can improve engine performance and reduce the level of engine damage which will increase the continuity of production activities. In the die casting division of PT Astra Honda Motor in the observation on the die casting machine 07 there were 45 times damage to the ladle component and 11 times the damage to the auto spray component. These two components are critical components of the 07 die casting machine. After testing the compatibility index and the good compatibility of the damage time data and repair time data to obtain distribution data distribution patterns, obtain the tablespoon component MTTF assessment results of 107,833 hours and auto spray components amounting to 314,226 hours. Whereas the MTTR value of the spoon component is 0.385 hours and the auto spray component is 0.766 hours. The next step is to look for critical component replacement time intervals with the age replacement model, to further review whether it is related to increased reliability, decrease in total downtime, and cost savings before preventive maintenance is carried out and after preventive maintenance is carried out.